Carbon-based perovskite solar cells with electron and hole-transporting/-blocking layers. (15th March 2023) - Yu, Wenjin; Zou, Yu; Zhang, Shining; Liu, Zishi; Wu, Cuncun; Qu, Bo; Chen, Zhijian; Xiao, Lixin
Abstract: Towards commercialization of perovskite solar cells (PSCs), further reducing the cost and increasing the stability of PSCs have been the most important tasks of researchers, as the efficiency of single-junction PSCs has reached a competitive level among all kinds of single-junction solar cells. Carbon-electrode-based PSCs (CPSCs), as one of the most promising constructions for achieving stable economical PSCs, now attract enormous attention for their cost-effectiveness and stability. Here, we briefly review the development of CPSCs and reveal the importance of n-i-p architecture for state-of-the-art CPSCs. However, despite their promising potential, challenges still exist in CPSCs in the n-i-p architecture, which mainly stem from the incompact contact of the hole-transporting layer (HTL)/carbon electrode. Thus, new carbon materials and/or novel manufacturing methods should be proposed. In addition, HTL is yet to be appropriate for state-of-the-art CPSCs because the fabrication of carbon electrode could result in the destruction of the underlayer. To further enhance the performance of CPSCs, both the HTL and electron transport layer as well as their interfaces with perovskite active layer need to be improved. We recommend that the perovskite active layer, with its long carrier lifetime, strong carrier transport capability, and long-term stability, is necessary as well for improved performance of CPSCs. We also highlight current researches on CPSCs and provide a systematic review of various types of regulation tools.